Is it necessary to evaluate urinary tract infection in children with lower respiratory tract infection?. (8th August 2020) - Kim, Jeong Min; Koo, Ja Wook; Kim, Hyo‐Bin
Abstract : Aim: Although the incidence of urinary tract infection (UTI) in children with lower respiratory tract infection (LRTI) has been reported as 3.1–10.0%, the exact concomitant prevalence is questionable. Here, we evaluated the prevalence and related risk factors of UTI associated with LRTI in children under 36 months of age. Methods: We retrospectively reviewed the medical charts of 1574 patients under 36 months of age who were hospitalised with LRTI from January 2017 to December 2019 in a single centre, Seoul, South Korea. Among them, we analysed 278 patients who showed fever and performed urine evaluation. Urine was collected by catheterisation in children under 24 months of age and by voided urine between 24 and 36 months of age. Results: The prevalence of concomitant UTI and LRTI was 13.6% in children under 24 months of age. Mean age was significantly younger in the UTI versus non‐UTI group (6.93 ± 7.26 months vs. 12.61 ± 11.70 months; P  < 0.001). When the participants were stratified by age, the prevalence of UTI was significantly higher in children younger than 24 months of age compared to older ones ( P = 0.006). UTIs were more prevalent in boys than in girls (14.6% vs. 5.8%, P = 0.018). Peak body temperature, fever duration, premature birth and detected respiratory virus type did not differ between groups. Conclusions: It is not uncommon for children with LRTI with fever to be accompanied by UTI. When evaluating for UTI in children with febrile LRTI, age and sex must be considered.